2015
DOI: 10.14710/bioma.17.2.61-67
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effect of Cyperus rotundus L. on Seed Germination and Initial Growth of Glycine max L. cv. Grobogan

Abstract: Allelopathy is a phenomenon of direct or indirect, beneficial or adverse effects of a plant on its own or another plant through the release of chemicals into the environment. This experiment was carried out to determine the allelopathic effect of Cyperus rotundus L. (purple nutsedge) tuber aqueous extract on seed germination and initial growth of Glycine max L. (soybean) seedlings. The experiment was performed in completely randomized (CRD) design with five replications, using a range of concentrations of aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
1
10
0
6
Order By: Relevance
“…More accumulation of total phenol in the soybean that got drought stress than that got watering showed that the application of exogenous H2O2 increased the accumulation of endogenous H2O2 (Table 1), which would induce the synthesis of phenol as defense mechanism toward the second stress, in the form of drought stress. This result is consistent with the research by Darmanti et al (2016Darmanti et al ( , 2018 that drought stress on soybean increases the endogenous H2O2 and total phenol accumulation.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…More accumulation of total phenol in the soybean that got drought stress than that got watering showed that the application of exogenous H2O2 increased the accumulation of endogenous H2O2 (Table 1), which would induce the synthesis of phenol as defense mechanism toward the second stress, in the form of drought stress. This result is consistent with the research by Darmanti et al (2016Darmanti et al ( , 2018 that drought stress on soybean increases the endogenous H2O2 and total phenol accumulation.…”
supporting
confidence: 94%
“…Basic fertilizer i.e. 1 g TSP, 0.5 g KCL and 0.3 g ZA added to each pot (Darmanti et al 2018). Three soybean seeds were grown in each pot.…”
Section: A Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that various weed species signi cantly inhibited wheat seedling growth (Dongre and Singh 2007). Additionally, purple nutsedge extracts decreased the weight and length of soybean seedlings (Darmanti et al 2015), and ragweed parthenium (Parthenium hysterophorus) residue signi cantly inhibited radish (Raphanus sativus) and mustard (Brassica campestris) seedling length and dry weight (Batish et al 2005). Similarly, aqueous extracts and leachates of nutgrass (Cyperus rotundus) inhibited rice seedlings growth (Quayyum et al 2000).…”
Section: Inhibitory Effects Of Weeds On Switchgrass Seedling Growthmentioning
confidence: 98%
“…Weed allelopathy can alter crop physiological functions, such as their enzymatic activity, protein synthesis, respiration, and cell division and enlargement, and can thereby substantially reduce crop germination (Zohaib et al 2016). For example, aqueous extracts of purple nutsedge (Cyperus rotundus) increased germination time and decreased the germination index of soybean (Glycine max) seedlings (Darmanti et al 2015).…”
Section: Allelopathic Effects Of Weeds Root Aqueous Extracts On Switchgrass Germinationmentioning
confidence: 99%